2022
DOI: 10.3390/f13071057
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Equations for the Biomass Estimation of Calophyllum inophyllum L. in Java, Indonesia

Abstract: Reliable data on CO2 quantification is increasingly important to quantify the climate benefits of forest landscape restoration and international commitments, such as the Warsaw REDD+ Framework and Nationally Determined Contributions under the Paris Agreement. Calophyllum inophyllum L. (nyamplung as a local name or tamanu tree for the commercial name) is an increasingly popular tree species in forest landscape restoration and bioenergy production for a variety of reasons. In this paper, we present allometric eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Trees in 60 -<70 cm dbh contributed 47% of the AGB fractions. Above this diameter range, the AGB fractions decrease, this could be related to the lesser tree density of the diameter range and also to the hollowstemmed Ficus strangler which reduced the contribution of large diameter classes on ABG [13]. Furthermore, species contribution to total biomass (AGB and BGB) can be seen in Figure 4.…”
Section: Resultsmentioning
confidence: 92%
“…Trees in 60 -<70 cm dbh contributed 47% of the AGB fractions. Above this diameter range, the AGB fractions decrease, this could be related to the lesser tree density of the diameter range and also to the hollowstemmed Ficus strangler which reduced the contribution of large diameter classes on ABG [13]. Furthermore, species contribution to total biomass (AGB and BGB) can be seen in Figure 4.…”
Section: Resultsmentioning
confidence: 92%
“…Each tree in the measurement plot was recorded for species and measured for DBH. Aboveground biomass per tree was calculated using the allometric equation developed by Basuki, Leksono, Baral, Andini, Wahyuni, Artati, Choi, Shin, Kim, Yang, Samsudin and Windyarini [11] for Tamanu species, i.e. :…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Tamanu, a plant species found in abundant numbers along coastal parts of tropical areas, has garnered significant interest due to its various noteworthy attributes [4]. These include its valuable timber [5], medicinal capabilities [6,7], biodiesel potential [8,9], and its capacity to trap considerable quantities of carbon [10,11]. The forestry sector has various mitigation alternatives at its disposal, including the extension of carbon retention in harvested wood products, product substitution, and the production of biomass for bio-energy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Soil C stock for the 0-60 cm soil layer differs among different land uses and regions". Nair et al [11,12] noted that "C stock in the 0-60 cm soil layer is 121-123 t ha −1 for tropical forests and 110-117 t ha −1 for tropical savanna". "The results obtained from various studies on agroforestry practices in diverse ecological conditions showed that treebased agricultural systems, compared to treeless systems, stored more carbon in deeper soil layers near the tree than away from the tree; higher soil organic carbon content was associated with higher species richness and tree density" [11].…”
Section: Introductionmentioning
confidence: 99%